Mystical Vision in William Blake’s Poetry: A Study of Symbolism and Spiritual Themes (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The poetry of William Blake will be the subject of this critical examination, with a particular emphasis on the spiritual themes and symbols that are present in his work. In order to provide the audience with an understanding of the significance of symbols and imagery in Blake's spirituality and mysticism, the objective of this review is to educate them. There are hidden meanings that Blake often conveys via the use of imagery and symbols. These hidden meanings reflect the mystical and romantic elements of human life included within his poetry. Symbolism theory, which investigates Blake's use of symbols to transmit esoteric and spiritual meanings, serves as the primary theoretical foundation for this inquiry.via the use of a documentary approach, this investigation identifies portions within Blake's poetry that depict his mystical vision via the utilization of imagery and symbols. A deep dive into Blake's symbolism is included in this review, along with a discussion of his romantic and mystical poetry, which draws attention to the distinctive approach that Blake takes to dealing with spiritual matters. Poetry is not the only literary form that might potentially benefit from more study on the usage of symbols and images; plays, short stories, and novels are all strong possibilities for this kind of research. It is possible that more research into this field may assist in shedding light on the spiritual and symbolic components that are present in Blake's work across the literary canon.